Acrania case in a lamb - Erol ALAÇAM; Kamil SEYREK (Eurasian Journal of Veterinary Sciences)
A case of acrania was observed in a Merino lamb. The lamb was one of the twin male fetuses of the Merino sheep with her third lambing. The fetus was 3915 g in weight and 18 x 31 cm in diameters. The hair coat and other organs of the bo'dy were seen normal on macroscopic examination and under the x-ray photograhps except lack of the first four cervical vertebrates, cranium and maiformation of the pelvic bone.